Analisis Semiotika John Fiske terhadap Representasi Nilai Moderasi Beragama dalam Dialog Podcast Escape Episode 5 'Fenomena Islam dan Muslim (Munafik)' oleh Raymond Chin dan Ustadz Felix Siauw - Dewi Kartika; Gita Nurjayanti; Betty Mauli Rosa Bustam (Jurnal Indonesia Studi Moderasi Beragama, 2025)
Background: The dominance of conservative religious narratives on social media often triggers exclusivism and intolerance, especially among the younger generation. On the other hand, digital media such as podcasts are beginning to be used as alternative spaces for conveying religious messages reflectively and inclusively. Objectives: This study aims to analyse the representation of religious moderation values in the podcast as a form of reflective and contextual digital religious communication. Method: This study employs a descriptive qualitative approach with two analytical methods: thematic analysis using Taguette software and John Fiske's semiotic analysis as a theoretical framework for interpreting symbols and messages in podcast dialogues. Results: The eight central values of religious moderation, tawassuth, tasamuh, i'tidal, syura, anti-violence, tathawwur wa ibtikâr, tasdid, and wasathiyyah, are symbolically and contextually represented through reflective narratives, equal communication, and empathetic discussions between the speakers. Conclusion: Escape podcast episode 5 represents an adaptive narrative of religious moderation, bridging conservatism and religious liberalism, and opening up space for negotiating the meaning of Islam that is more relevant to the lives of the younger generation. Contribution: This study contributes to the development of literature on religious moderation and digital Islamic communication studies and serves as a reference for producing inclusive and contextual digital da'wah content in the era of media transformation.